2019
DOI: 10.1186/s12967-019-02173-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel glycolysis-related gene signature for predicting metastasis and survival in patients with lung adenocarcinoma

Abstract: Background: Lung cancer (LC) is one of the most lethal and most prevalent malignant tumors, and its incidence and mortality are increasing annually. Lung adenocarcinoma (LUAD) is the most common pathological type of lung cancer. Several biomarkers have been confirmed by data excavation to be related to metastasis, prognosis and survival. However, the moderate predictive effect of a single gene biomarker is not sufficient. Thus, we aimed to identify new gene signatures to better predict the possibility of LUAD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
150
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 37 publications
7
150
0
Order By: Relevance
“…These data were used to study the relationship between 15 genes and TME among patients with high versus low immune scores or stromal score groups using the ESTIMATE algorithm. Previous studies have reported that 9 out of the 15 immune genes associated with prognosis (S100A16, CRABP1, RBP2, FGF2, FPR2, BDNF, ANGPTL4, SEMA4B and VIPR1 [33][34][35][36][37][38][39][40][41]) are involved in the pathogenesis of lung cancer. The remaining six genes (IGKV4-1, IGKV6D-41, TNFRSF11A, INHA, IL11 and SCH3) have not been reported in the literature and may be used as potential biomarkers for lung cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…These data were used to study the relationship between 15 genes and TME among patients with high versus low immune scores or stromal score groups using the ESTIMATE algorithm. Previous studies have reported that 9 out of the 15 immune genes associated with prognosis (S100A16, CRABP1, RBP2, FGF2, FPR2, BDNF, ANGPTL4, SEMA4B and VIPR1 [33][34][35][36][37][38][39][40][41]) are involved in the pathogenesis of lung cancer. The remaining six genes (IGKV4-1, IGKV6D-41, TNFRSF11A, INHA, IL11 and SCH3) have not been reported in the literature and may be used as potential biomarkers for lung cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study reported an immune-related signature [17], which AUC of 1-(0.78) and 3-(0.76) year was also lower than that of this study. In addition, Zhang et al constructed a glycolysis-related gene prognostic signature with the AUC = 0.72 [18]. Meanwhile, a research developed a autophagy-related gene prognostic signature with the AUC = 0.615 [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the initiation and progression of hepatocellular carcinoma, genetic factors usually play an important role. Meanwhile, mRNA gene signature based on a certain characteristic like glycolysis [11] and immune [12] have been developed for prognosis of cancers. In this research, we explored specific function to identify genes by GSEA that could predict the survival of HCC patients.…”
Section: Discussionmentioning
confidence: 99%